If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7p + -1(3p + 4) = -2p + -1 + 10 Reorder the terms: 7p + -1(4 + 3p) = -2p + -1 + 10 7p + (4 * -1 + 3p * -1) = -2p + -1 + 10 7p + (-4 + -3p) = -2p + -1 + 10 Reorder the terms: -4 + 7p + -3p = -2p + -1 + 10 Combine like terms: 7p + -3p = 4p -4 + 4p = -2p + -1 + 10 Reorder the terms: -4 + 4p = -1 + 10 + -2p Combine like terms: -1 + 10 = 9 -4 + 4p = 9 + -2p Solving -4 + 4p = 9 + -2p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '2p' to each side of the equation. -4 + 4p + 2p = 9 + -2p + 2p Combine like terms: 4p + 2p = 6p -4 + 6p = 9 + -2p + 2p Combine like terms: -2p + 2p = 0 -4 + 6p = 9 + 0 -4 + 6p = 9 Add '4' to each side of the equation. -4 + 4 + 6p = 9 + 4 Combine like terms: -4 + 4 = 0 0 + 6p = 9 + 4 6p = 9 + 4 Combine like terms: 9 + 4 = 13 6p = 13 Divide each side by '6'. p = 2.166666667 Simplifying p = 2.166666667
| 30+18x=21.54 | | 20x^3+100x^2=0 | | 34x-16+15x^2=0 | | 9x+10=-2(x+3)+3x | | r^4=3r^3+18r^2 | | 10x+8=65+13x | | y^2=x+1 | | 12=-14B+3B | | 0.14-0.01(x-2)=-0.02(3-x) | | X-x(3x-5)=x-2(x(x)+x)-x(x)-14 | | S=2(3.14)rh+(3.14) | | y=14-2y | | -6-3=9r-6 | | 0.10(x+10)+0.70x=17 | | 4(2x-5)=3x+13 | | 10P+8=5P-2 | | 13-22=-3x | | 16-3b=0 | | 5=7Y-5Y-3 | | y^2+13y+12= | | 16-36=0 | | 10B-11B=0 | | 2(-4+p)=-8.2+1.8p | | -4=-9+8-29 | | x^2+47x+56=0 | | H(x)=2x^3+5x^2-31x-15 | | -15n^2+13=-10n^2-6n | | 6x(3x-4)(2x+5)= | | x^6-243=0 | | -4=9+8-29 | | 3n^2=-8 | | 51a-56=44 |